Tindak Tutur Ilokusi dalam Tayangan Mata Najwa "Eksklusif: Ganjar Pranowo dan Piala Dunia" (Kajian Pragmatik) - Novianti, Fitria Friska (Kajian Bahasa dan Sastra (KABASTRA), 2024)
Speech acts are speech behaviors that have an impact on the effectiveness of communication. The speech act itself has three types, namely locution, illocution, and perlocution. Illocutionary speech acts are classified into five functions, including assertive, directive, expressive, declarative, and commissive. This research aims to describe the results of illocutionary speech acts in the Mata Najwa talk show dialog, using the five functions of illocutionary speech acts. This research uses a qualitative descriptive method, the subject of this research is the speech of Najwa Shihab and Ganjar Pranowo contained in the Mata Najwa program with the title "Exclusive, Ganjar Pranowo and the World Cup". The data collection technique is done by using listening and note taking technique. The object of this research is all speech acts contained in the dialog. The most data were found in the assertive function illocutionary speech acts, which is fifteen data and the least data of declarative function speech acts were found, which is one data.